1971
DOI: 10.1071/ch9712173
|View full text |Cite
|
Sign up to set email alerts
|

The structure of squamulosone, a new sesquiterpene ketone from Phebalium squamulosum

Abstract: Squamulosone, C15H22O, a new sesquiterpene ketone occurring in Phebalium squamulosum, has been shown to have the structure (1) on chemical and spectroscopic evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1971
1971
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…We found an additional oxidation product of ledene (92), the aromadendren-9-one 135, which was isolated in 1971 from the shrub Phebalium squamulosum by Batey et al 43 and named`squamulosone'. Its enantiomer, called`millecrone B', was found recently in an extract of the nudibranch Leminda millecra.…”
Section: Aromadendrane Derivativesmentioning
confidence: 95%
“…We found an additional oxidation product of ledene (92), the aromadendren-9-one 135, which was isolated in 1971 from the shrub Phebalium squamulosum by Batey et al 43 and named`squamulosone'. Its enantiomer, called`millecrone B', was found recently in an extract of the nudibranch Leminda millecra.…”
Section: Aromadendrane Derivativesmentioning
confidence: 95%
“…Hence, to the best of our knowledge, the purest natural source of dihydrotagetone is the essential oil of these two subspecies of P. glandulosum. [4] and Brophy et al [3a] did not yield squamulosone, a sesquiterpenoid ketone first reported by Batey et al [8] from P. squamulosum collected from Narrabeen, New South Wales. This Sydney Basin population belongs in the type subspecies, P. squamulosum subsp.…”
mentioning
confidence: 99%
“…In the current study, squamulosone was detected at low concentration in the hydrodistilled EO but not at all in the DCM extracts most likely due to at a concentration lower than our minimum peak area used in quantification. Squamulosone, a sesquiterpene ketone, shares the same structural skeleton to the alcohol ledol [16,17]. Squamulosone has previously only been identified in extracts and essential oils from Phebalium squamulosum (Rutaceae), where it was first described [17,18].…”
Section: Gc-ms Analysismentioning
confidence: 99%
“…Squamulosone, a sesquiterpene ketone, shares the same structural skeleton to the alcohol ledol [16,17]. Squamulosone has previously only been identified in extracts and essential oils from Phebalium squamulosum (Rutaceae), where it was first described [17,18].…”
Section: Gc-ms Analysismentioning
confidence: 99%